GAYA KEPEMIMPINAN TRANSFORMASIONAL MEMODERASI PENGARUH KOMITMEN GURU DAN KOMPETENSI PROFESIONAL TERHADAP KINERJA GURU SMP NEGERI SE-RAYON JUWANA KAB. PATI - Nuryastuti, Emy; Suhari, Yohanes (Jurnal Ilmiah Telaah Manajemen, 2017)
The purpose of this study was to examine the role of transformational leadership to moderate the influence of teachers' commitment and professional competence of the teacher performance at Junior High School in Juwana administrative district Pati regency. The specific objective of this study was to examine the moderating influence of transformational leadership commitment and professional competence of teachers on teacher performance at Junior High School in Juwana administrative district Pati regency.. The population in this study were obtained from teachers in Juwana administrative district Pati regency many as 142 people. The analysis technique used is multiple linear regression model with quasi moderation. The results showed that the commitment of teachers affect the performance of teachers, professional competence affect the performance of teachers, transformational leadership style affect the performance of teachers, transformational leadership to support the influence of commitment of teacher on teacher performance, and transformasional leadership to support the influence on the profesional competence of teachers performance. Keywords: teacher commitment, professional competence, leadership style and teacher performance.